The Role of Human Papilloma Virus (HPV) Infection in Non-Anogenital Cancer and the Promise of Immunotherapy: A Review. (3rd September 2014) - Cobos, Chris; Figueroa, José A.; Mirandola, Leonardo; Colombo, Michela; Summers, Gabby; Figueroa, Alejandro; Aulakh, Amardeep; Konala, Venu; Verma, Rashmi; Riaz, Jehanzeb; Wade, Raymond; Saadeh, Charles; et al.
<x xml:space="preserve">Abstract</x> Over the past 30 years, human papilloma virus (HPV) has been shown to play a role in the development of various cancers. Most notably, HPV has been linked to malignant progression in neoplasms of the anogenital region. However, high-risk HPV has also been suggested to play a significant role in the development of cancers in other anatomic locations, such as the head and neck, lung, breast and bladder. In 2006, the first vaccine for HPV, Gardasil, was approved for the prevention of subtypes 6, 11, 16 and 18. A few years later, Cevarix was approved for the prevention of subtypes 16 and 18, the HPV subtypes most frequently implicated in malignant progression. Although increased awareness and vaccination could drastically decrease the incidence of HPV-positive cancers, these approaches do not benefit patients who have already contracted HPV and developed cancer as a result. For this reason, researchers need to continue developing treatment modalities, such as targeted immunotherapies, for HPV-positive lesions. Here, we review the potential evidence linking HPV infection with the development of non-anogenital cancers and the potential role of immunotherapy in the prevention and eradication of HPV infection and its oncogenic sequela.